Shadowing the elected: mixed-member incentives to locally oriented parliamentary questioning. Issue 2 (2nd April 2016) - Papp, Zsófia
ABSTRACT: It is often suggested in the case of mixed-member electoral systems that legislators with close ties to the single member districts (SMDs) are more constituency oriented than those with weaker ties. This article investigates the effect of three career-related variables (mandate type, tier of candidacy and the number of formerly held SMD mandates) on the constituency orientation of national representatives. The analysis relies on a comprehensive database containing MP-level career information and the number of locally relevant written questions submitted between 2010 and 2013 in the Hungarian parliament. Contrary to expectations, the results suggest that SMD candidates who were elected on party lists tend to ask a larger number of questions with local relevance than SMD MPs. Furthermore, MPs with considerable SMD experience are found to be more constituency oriented only among those who gained their mandates in an SMD.